Les rêves prophétiques de Marie de l’Incarnation (1599-1672) - Bonesso, Amandine (Ponti/Ponts, 2021)
The research examines the dream experiences described by Marie Guyard de l’Incarnation (1599-1672) in her spiritual autobiography, Relation of 1654. It is the analysis of the enunciation and the elaboration of space and time in recounting these two spiritual phenomena, to emphasize some aspects of this autobiographic and mystic report. Dreams reveal themselves as experiences of transition between the real and the supernatural implying a subject split in two and a kind of transfer of space and time, and revealing their prophetic nature.